Is a New 'Planning 3.0' Paradigm Emerging? Exploring the Relationship between Digital Technologies and Planning Theory and Practice. (14th March 2020) - Potts, Ruth
ABSTRACT: In recent decades cities and urban planning have become increasingly digitised, complex and data rich. Despite this, the planning theory literature has largely ignored the role and impact of information and communication technologies in shaping planning's ontologies, epistemologies, and methodologies. This article explores empirical studies and three major planning paradigms, to explore the changing role and influence of information and communication technologies (ICTs) on planning theory and practice. Based on this, the paper argues that ICTs are driving a shift towards a more interactive, intelligent, self-organising, and interconnected planning paradigm.